Targeted insertion of an anti-CD2 monoclonal antibody transgene into the GGTA1 locus in pigs using FokI-dCas9 - Mark B. Nottle (Nature Portfolio, 2017)
Abstract Xenotransplantation from pigs has been advocated as a solution to the perennial shortage of donated human organs and tissues. CRISPR/Cas9 has facilitated the silencing of genes in donor pigs that contribute to xenograft rejection. However, the generation of modified pigs using second-generation nucleases with much lower off-target mutation rates than Cas9, such as FokI-dCas9, has not been reported. Furthermore, there have been no reports on the use of CRISPR to knock protective transgenes into detrimental porcine genes. In this study, we used FokI-dCas9 with two guide RNAs to integrate a 7.1 kilobase pair transgene into exon 9 of the GGTA1 gene in porcine fetal fibroblasts. The modified cells lacked expression of the αGal xenoantigen, and secreted an anti-CD2 monoclonal antibody encoded by the transgene. PCR and sequencing revealed precise integration of the transgene into one allele of GGTA1, and a small deletion in the second allele. The cells were used for somatic cell nuclear transfer to generate healthy male knock-in piglets, which did not express αGal and which contained anti-CD2 in their serum. We have therefore developed a versatile high-fidelity system for knocking transgenes into the pig genome for xenotransplantation purposes.